2014
DOI: 10.1111/1471-0307.12146
|View full text |Cite
|
Sign up to set email alerts
|

Κ‐CN gene polymorphism in Nili‐ravi buffalo, Achai and Sahiwal cattle of Pakistan

Abstract: Kappa-casein (j-CN) is the subtype of casein protein, an important constituent of bovine milk protein. The current study was undertaken to investigate the genetic polymorphism in j-CN gene of Nili-ravi buffalo, Achai and Sahiwal cattle of Pakistan using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique. The Nili-ravi buffalo was found to be monomorphic (genotype BB only) for j-CN gene. Achai cattle were polymorphic for j-CN (having three genotypes AA, AB and BB) with a fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Similar results of monomorphic "BB" were obtained in Nili-Ravi buffaloes using PCR-RFLP analysis with of (443 bp) fragment of PCR product of κ-CN with HindIII restriction enzyme as reported by Ghafoor et al (2015). Also, the restriction digestion analysis of (350 bp) PCR product of κ-CN with HinfI enzyme referred to the presence of only one genotype of "BB" in Nagpuri buffaloes of India as mentioned by Nair et al (2011).…”
Section: Allelic and Genotypic Frequencies Of Studied Genessupporting
confidence: 78%
See 2 more Smart Citations
“…Similar results of monomorphic "BB" were obtained in Nili-Ravi buffaloes using PCR-RFLP analysis with of (443 bp) fragment of PCR product of κ-CN with HindIII restriction enzyme as reported by Ghafoor et al (2015). Also, the restriction digestion analysis of (350 bp) PCR product of κ-CN with HinfI enzyme referred to the presence of only one genotype of "BB" in Nagpuri buffaloes of India as mentioned by Nair et al (2011).…”
Section: Allelic and Genotypic Frequencies Of Studied Genessupporting
confidence: 78%
“…These findings showed that the majority of studied individuals were heterozygous, i.e., these populations depended on outbreeding or mating with migrants. In disagreement with these results, Ghafoor et al (2015) noticed that there were no heterozygotes observed within Nili-ravi buffaloes due to all animals had homozygous genotype "BB".…”
Section: Heterozygosity and Inbreeding Coefficient (F Is ) Of κ-Cn Genementioning
confidence: 73%
See 1 more Smart Citation
“…Similar to our results, Egyptian buffalo were reported to be BB monomorphic (Karima et al 2010). BB monomorphic buffaloes were also reported in Pakistan (Riaz et al 2008;Ghafoor et al 2014), Pandharpuri breed of India (Shende et al 2009), South Kanara and Surti breed of India (Gangaraj et al 2008) and Murrah breed of Brazil and their crossings (Otaviano et al 2008). All investigations, reporting BB monomorphic buffalo, were conducted by PCR-RFLP analyses using restriction enzymes such as HindIII and HinfI used for investigating polymorphism in cattle j-CN.…”
Section: Discussionmentioning
confidence: 99%
“…The kappa casein gene lies at chromosome 6 of bovine and at chromosome 4 of sheep and goat. Casein fraction of milk proteins significantly influences the composition and physic-chemical properties of milk (Grosclaud 1988) and milk production (Ghafoor et al 2014).…”
Section: Introductionmentioning
confidence: 99%